2023
DOI: 10.2166/wpt.2023.024
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of irrigation water requirement and irrigation scheduling for major crops using the CROPWAT model and climatic data

Abstract: The world is facing an acute water shortage. The present irrigation techniques used in the Hyderabad district, Pakistan, are not demand-driven. The present study was carried out to determine the crop water requirement (CWR), irrigation water requirement (IWR), and irrigation scheduling for major crops grown in the Hyderabad district using the CROPWAT model based on climatic, soil, and crop data. The analysis revealed that the total CWR for the entire growing season for sugarcane, banana, cotton, and wheat were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…CMRSET ETa compares well both in terms of magnitude and seasonality, although in Punjab's CMRSET's peak in Rabi (October to March) happens in March and in April for ETLook. Crop calendars state that the most widespread Rabi crop in the region, wheat, is harvested in April, however, ETa reaches its peak in March (Soomro et al, 2018). Similar seasonality of double cropping systems is not observed in SEBAL.…”
Section: Blending Of Modis With Landsat Vegetation Indicesmentioning
confidence: 90%
“…CMRSET ETa compares well both in terms of magnitude and seasonality, although in Punjab's CMRSET's peak in Rabi (October to March) happens in March and in April for ETLook. Crop calendars state that the most widespread Rabi crop in the region, wheat, is harvested in April, however, ETa reaches its peak in March (Soomro et al, 2018). Similar seasonality of double cropping systems is not observed in SEBAL.…”
Section: Blending Of Modis With Landsat Vegetation Indicesmentioning
confidence: 90%
“…While the use of efficient irrigation systems by lowland rice farming communities is highly desired, it alone is not enough [1] [36]. A recent study by [37] on the irrigation of wheat, rice, sugarcane, berseem, sorghum and maize in Pakistan revealed that about 60% of irrigation water is lost through over irrigation and this is mainly caused by lack of farmers' knowledge about irrigation scheduling. Regardless of the irrigation method used, appropriate irrigation scheduling has long been known to help farmers apply water appropriately [38].…”
Section: Rice Production In Sub-saharan Africamentioning
confidence: 99%
“…In this situation, the only choice remaining is to manage the available water resources with best management practices. Approximately 93% of freshwater resources are used in agriculture, and any effort to improve water use efficiency (WUE) in this sector would result in saving water for other rational uses (Mohyuddin & Ahmed, 2008; Soomro et al, 2018). In Pakistan, more than 60% of the water used in agriculture is lost during conveyance through seepage from irrigation channels and during application on fields (Soomro et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 93% of freshwater resources are used in agriculture, and any effort to improve water use efficiency (WUE) in this sector would result in saving water for other rational uses (Mohyuddin & Ahmed, 2008; Soomro et al, 2018). In Pakistan, more than 60% of the water used in agriculture is lost during conveyance through seepage from irrigation channels and during application on fields (Soomro et al, 2018). Seepage from the irrigation network and over‐irrigation have resulted in an increase in water table depths (WTDs) in many areas.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation